2001
DOI: 10.4049/jimmunol.166.11.6608
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide Induces the Development of Early Myeloid Cells Suppressing Tumor Cell Growth by a Nitric Oxide-Dependent Mechanism

Abstract: Adoptive immunotherapy with cyclophosphamide (Cy) increases the host resistance against tumor growth. The precise mechanism(s) by which this therapy enhances tumor suppression is unclear. Cy induces the development of early myeloid cells that may be strongly antiproliferative through NO production. These cells are similar to the natural suppressor cells found in normal bone marrow with a potential antitumor effect. Here we have addressed whether the development of NO-producing cells may be involved in this tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 57 publications
5
69
2
Order By: Relevance
“…83,84 Recently, low-dose CTX treatment of mice spontaneously developing melanomas led to an accumulation of inflammatory mediators, such as GM-CSF, IL-1b, IL-5, IL-10, IFN-g and TNF-a, in skin tumors and metastatic LNs, inducing accumulation and activation of MDSCs that abrogated CTX antitumor effects. 85 Other reports, however, show that CTX induces early myeloid effector cells that may inhibit tumor cell growth through nitric oxide (NO) release, 86 and that metronomic CTX plus gemcitabine mitigates Treg-and MDSC-mediated immunosuppression and elicits antitumor immunity in vivo. 87 Among taxanes, paclitaxel specifically impairs viability and cytokine production in FOXP3 þ Treg cells, but not in FOXP3 À CD4 effector cells.…”
Section: Effects On Regulatory Subsets and Pathwaysmentioning
confidence: 99%
“…83,84 Recently, low-dose CTX treatment of mice spontaneously developing melanomas led to an accumulation of inflammatory mediators, such as GM-CSF, IL-1b, IL-5, IL-10, IFN-g and TNF-a, in skin tumors and metastatic LNs, inducing accumulation and activation of MDSCs that abrogated CTX antitumor effects. 85 Other reports, however, show that CTX induces early myeloid effector cells that may inhibit tumor cell growth through nitric oxide (NO) release, 86 and that metronomic CTX plus gemcitabine mitigates Treg-and MDSC-mediated immunosuppression and elicits antitumor immunity in vivo. 87 Among taxanes, paclitaxel specifically impairs viability and cytokine production in FOXP3 þ Treg cells, but not in FOXP3 À CD4 effector cells.…”
Section: Effects On Regulatory Subsets and Pathwaysmentioning
confidence: 99%
“…There is evidence from a number of pre-clinical and clinical studies that lowdose cyclophosphamide (CY) administered prior to vaccination is of benefit to cancer patients most likely through inhibition of Tregs and subsequently enhanced immune responses and/or clinical response to vaccination. [45][46][47][48][49][50][51] In addition, positive immunomodulatory effects of CY on dendritic cells [52][53][54][55] , other antigen presenting cells 52 , tumor infiltrating cells 53,55,56 and MDSCs 52,57,58 have been shown in in vitro experiments as well as in animal models.…”
Section: Adjuvants/immunostimulantsmentioning
confidence: 99%
“…Early results suggested that cyclophosphamide is an inhibitor of suppressor T cells induced in tumour bearers (14). Further studies have showed that cyclophosphamide induces development of spleen early myeloid cells (15). Recently (16), it has been demonstrated that these myeloid suppressor Gr1 + /CD11b + cells accumulate in the spleens of tumour-bearing animals and contribute to immunosupression in tumour bearers.…”
Section: Introductionmentioning
confidence: 99%